Desires and beliefs: the development of second-order Theory of Mind reasoning in preschoolers and in school-age children - Bianco, Federica; Cornaggia, Alessia; Massaro, Davide; Marchetti, Antonella; Castelli, Ilaria (Frontiers in Psychology, 2025)
IntroductionTheory of Mind development is crucial for social life. Most studies on the development of this skill have focused on first-order recursive thinking, while the transition to second-order thinking remains relatively unexplored.MethodsTo address this gap, we administered a novel second-order Theory of Mind task to 59 children between the ages of 5 and 8 years. This task manipulated desires (desire to obtain, “positive desire,” vs. desire to avoid, “negative desire”) and beliefs (true vs. false) based on previous studies of first-order scaling.ResultsResults indicate that the tasks involving positive desire seem to be easier than negative counterparts, and that the tasks involving true belief are easier than those involving false belief. All children performed below chance level in negative desire and in false belief conditions, while only older participants performed above chance level in true belief – positive desire condition. There was also a significant main effect favoring positive desire and true belief.DiscussionOur findings provide preliminary evidence for the developmental acquisitions of second-order recursive thinking about the understanding of desires and beliefs.